Operating characteristics of supercritical carbon dioxide high speed tilting pad bearings considering inertia effect - Yi, Shuxiang; Wang, Xiaojing; Chen, Sheng; Yuan, Weimin (Advances in mechanical engineering, 2023)
Some degree of inertia effect on the bearing film is inevitable for high density supercritical carbon dioxide (S-CO2) working as a lubricant in high speed rotor operating conditions. This paper aims to reveal the influence of inertia effect on static and dynamic performances of the S-CO2 tilting pad bearings. Numerical results demonstrate that inertia effect on the lubricating film of the top pad is more pronounced. The peak pressure of all pads is increased at a high reduced Reynolds number compared with the inertialess condition, while the influence of inertia effect on the dynamic coefficient is weak. The theoretical model including inertia effect presented in this study can more accurately evaluate the performance of high speed S-CO2 tilting pad bearings.